The structure of the polar vortex - Schoeberl, Mark R.; Lait, Leslie R.; Newman, Paul A.; Rosenfield, Joan E. (1992)
The paper develops a comparative picture of the 1987 Southern Hemisphere and 1989 Northern Hemisphere lower stratospheric, polar vortex circulation and constituent distributions as observed by the Airborne Antarctic Ozone Experiment, August 17-September 22, 1987, and Airborne Arctic Stratospheric Expedition, January 3-February 19, 1989 aircraft campaigns. Overall, both polar vortices define a region of highly isolated air, where the exchange of trace gases occurs principally at the vortex edge through erosional wave activity. Aircraft measurement showed that between 50 and 100 mbar, horizontally stratified long-lived tracers such as N2O are displaced downward 2-3 km on the cyclonic (poleward) side of the jet with the meridional tracer gradient sharpest at the jet core. Eddy mixing rates, computed using parcel ensemble statistics, are an order of magnitude or more lower on the cyclonic side of the jet compared to those on the anticyclonic side. Poleward zonal mean meridional flow on the anticyclonic side of the jet terminates in a descent zone at the jet core.